Significant role of anionic behavior of cocoyl glutamate on lead(II) ion adsorption towards activated carbon adsorbent from cigarette butts - Moh Zeinur Ridho; Retno Pertiwi; Eldo Delta Bagaskara; Raya Rambu Rambani; Chika Synthia Pitaloka; Fanta Mei Wahyuni; Istiqomah Rahmawati; Muhammad Reza (Case Studies in Chemical and Environmental Engineering)
Cigarette butts are one of the most abundant waste in the world, being dangerous due to non-biodegradable behavior and highly toxic. Cigarette butts can be converted to activated carbon (CA) which can be used as an adsorbent. However, the synthesized CA lacks functional groups facilitating the interaction with adsorbate, like heavy metal. This paper investigates the effect of Disodium Cocoyl Glutamate (DCG) modification on CA towards lead(II) ion adsorptions. CA was synthesized from cigarette butt waste through several vital processes, like flash carbonization and activation. The surfactant used in this study was DCG due to its natural and anionic behavior, with varied concentrations (0.1, 1, and 10 % (v/v)). Infrared spectroscopy revealed that the structure of both CA and CA-DCG mainly consists of aromatic rings functionalized by several oxygen functional groups, such as carbonyl and hydroxyl groups. Adding DCG increases the number of carbonyl groups in the CA confirmed by infrared and elemental analysis data. The obtained CA-DCGs have an amorphous property and a slightly porous structure. The presence of DCG also affects CA-DCG crystallinity, which increases the amorphous content as the concentration of DCG increases. The adsorption results show that the equilibrium removal efficiency significantly increased from 25 % to 99 % as DCG was introduced to the CA. CA-DCG 0.1 % demonstrated the highest maximum adsorption capacity of 9.89 mg/g. The presence of DCG markedly enhances the affinity of CA towards lead(II) ions due to its anionic behavior. Based on these results, CA-DCG is potentially applied as a lead(II) ion adsorbent. It also could reduce the existing cigarette butt waste in the environment.